Prophylactic accessory renal artery coil embolization for prevention of type II endoleak following endovascular aneurysm repair: a case report - Ryosuke Nishie; Naoki Toya; Soichiro Fukushima; Eisaku Ito; Yuri Murakami; Tadashi Akiba; Takao Ohki (Surgical Case Reports, 2017)
Abstract Background Prior reports indicate that intentional coverage of the accessory renal arteries (ARAs) with a diameter larger than 3 mm during endovascular aneurysm repair (EVAR) increases risk of additional treatment for type II endoleak. Here, we report a case of prophylactic coil embolization for a 4 mm ARA originating from an abdominal aortic aneurysm. Case presentation A 76-year-old woman was admitted to our hospital after noticing an abdominal pulsatile mass. Computed tomography (CT) imaging revealed an abdominal aortic aneurysm (AAA) with a maximum diameter of 53 mm. Preoperative CT scan showed a right ARA, 4 mm in diameter, which was considered likely to lead to type II endoleak following EVAR. ARA coil embolization was performed at the time of EVAR. We observed no endoleaks and no infarct of the inferior pole of the right kidney on completion angiography. The postoperative course was uneventful, and the patient was discharged 7 days later. Postoperative eGFR (58.4 ml/min) was not significantly different from preoperative level (56.7 ml/min). After EVAR, blood pressure was under control, and no additional anti-hypertensive medicines were required. Postoperative enhanced CT image showed that the distal portion of the ARA was well perfused without type II endoleak from ARA. Conclusions Prophylactic coil embolization for a large ARA originating from an abdominal aortic aneurysm appears to be safe and effective in preventing type II endoleak following EVAR.